On the Position of the Organic Unbuilt Nature in the Poetics and Ideology of Eastern Adriatic Futurism - Pužar, Aljoša (Poznańskie Studia Slawistyczne, 2022)
The article offers an overview of lesser-known aspects of the Eastern Adriatic futuristic avant-garde in a broader sense: both the futuristic movement itself and the phenomena that relied on it in conventional interpretations. Selected episodes relate to the examination of the futuristic relationship to the organic unbuilt nature. Emphasis is placed on the comparative image of this multicultural and multilingual literary region, beyond national historiographical conventions.